2015
DOI: 10.17224/energagric.2015v30n1p33-40
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças Comportamentais De Poedeiras Em Diferentes Ambientes Térmicos

Abstract: RESUMO:O microclima no interior da instalação avícola é um dos fatores responsáveis pelo sucesso do empreendimento e afeta o comportamento da ave. Assim, o objetivo deste experimento foi verificar como o ambiente térmico proporcionado em aviários influencia o comportamento das poedeiras. O experimento foi realizado em galpões de escala reduzida e distorcida com poedeiras de idade entre 30 e 32 semanas. As aves foram criadas em boxes com cama de maravalha, poleiro e ninho, em dois grupos diferentes (6 e 12 aves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…After hearing the sound, the birds approached the feeder and, for a few minutes, this was the prevailing behavior in the barns. Using the scanning technique, Pereira et al (2015a) did not find a significant difference in the frequency of feeding behavior either. However, other authors, such as Barbosa Filho et al (2007) and Silva et al (2006), using the individual bird banding technique, reported a decrease in the frequency of feeding behavior with temperature increase.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…After hearing the sound, the birds approached the feeder and, for a few minutes, this was the prevailing behavior in the barns. Using the scanning technique, Pereira et al (2015a) did not find a significant difference in the frequency of feeding behavior either. However, other authors, such as Barbosa Filho et al (2007) and Silva et al (2006), using the individual bird banding technique, reported a decrease in the frequency of feeding behavior with temperature increase.…”
Section: Resultsmentioning
confidence: 67%
“…Zootec., 46(3): [175][176][177][178][179][180][181][182][183][184]2017 the temperature is within the range required by the animals (Pereira et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that the egg production and behavior of layers affected by the thermal environment of the shed (Silva et al 2013;Castilho et al 2015;Nayak et al 2015;Pereira et al 2015). The upper limit of the thermoneutrality and thermal comfort zones of chickens (both broilers and layers) was established as below 30ºC (Freeman, 1988;Costa, 1994;Alves, 2006;Pereira & Nääs, 2008;Baeta & Souza, 2010).…”
Section: Climate Change In Layer Poultry Farming: Impact Of Heat Wavementioning
confidence: 99%
“…"Heat waves can also be characterized as periods of a sudden increase of environmental temperature, which intensity and duration may vary (Zuo et al, 2015). In egg production, Pereira et al (2015) reported that environmental temperature affects hen behavior. In the study of Riquena (2017), layer mortality during heat waves characterized and predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Since most broilers and laying hens are commercially reared in environments with artificial light, adequate lighting management on commercial farms is essential for optimizing bird welfare and production efficiency (Silva et al, 2013;Pereira et al, 2015). Because light influences the behavior of reproducing poultry and commercial parameters, visual stimuli are a powerful management tool in the hands of the producer.…”
Section: Introductionmentioning
confidence: 99%